Augmented-reality guided treadmill training as a modality to improve functional mobility post-stroke: A proof-of-concept case series. Issue 8 (17th November 2021) - Enam, Nabela; Veerubhotla, Akhila; Ehrenberg, Naphtaly; Kirshblum, Steven; Nolan, Karen J.; Pilkar, Rakesh
ABSTRACT: Objective : To provide a proof-of-concept for a novel stroke-gait-specific augmented reality (AR)-guided treadmill intervention by evaluating its effect on temporospatial and functional outcomes of mobility. Methods : Two females with hemiplegia post stroke were recruited for participation in a 4-week intervention, and a single healthy control was recruited for baseline comparisons. The stroke-intervention (SI) participant (aged 54-years), completed 12 sessions of AR-guided treadmill intervention. The stroke-control (SC) participant (aged 59-years) completed 12 sessions of conventional treadmill intervention. Temporospatial and functional mobility were assessed pre-intervention, post-intervention, and at 1-month follow-up. Physical ACtivity Enjoyment Scale (PACES) was administered post-intervention. Results : The SI participant showed clinically meaningful improvements in functional outcomes post-intervention and at 1-month follow-up (Berg balance score (BBS): +6 and +10 points; Dynamic Gait Index (DGI): +2 at post-intervention only; walking speed: +0.19 and +0.24 m/s; 6-minute walk test (6MWT): +51.9 and +38.9) respectively. The SC showed clinically meaningful improvements in BBS (+3 and +3) and walking speed (+0.06 at post-intervention). The PACES scores showed that the SI participant had a significantly higher (23 points) enjoyment level during the intervention compared to the SC participant. The SI participant was more asymmetric compared to the SC participant at pre and post-intervention visits. Conclusions : The SI participant showed greater improvement in functional assessments compared to the SC participant post intervention. The AR-guided approach may have added benefits compared to traditional treadmill training, while providing better customization, patient enjoyment, and engagement. Further investigation with a larger sample is warranted.